Copper‐Mediated Selenazolidine Deprotection Enables One‐Pot Chemical Synthesis of Challenging Proteins1. Issue 41 (4th September 2019) - Zhao, Zhenguang; Metanis, Norman
Abstract: While chemical protein synthesis has granted access to challenging proteins, the synthesis of longer proteins is often limited by low abundance or non‐strategic placement of cysteine residues, which are essential for native chemical ligations, as well as multiple purification and isolation steps. We describe the one‐pot total synthesis of human thiosulfate:glutathione sulfurtransferase (TSTD1). WT‐TSTD1 was synthesized in a C‐to‐N synthetic approach involving multiple NCL reactions, Cu II ‐mediated deprotection of selenazolidine (Sez), and chemoselective deselenization. The seleno‐analog Se‐TSTD1, in which the active site Cys is replaced with selenocysteine, was also synthesized with a kinetically controlled ligation with an N‐to‐C synthetic approach. The catalytic activity of the two proteins indicated that Se‐TSTD1 possessed only four‐fold lower activity than WT‐TSTD1, thus suggesting that selenoproteins can have physiologically comparable sulfutransferase activity to their cysteine counterparts. Abstract : All together now : A highly efficient Cu II ‐mediated deprotection of selenazolidine was applied to the one‐pot synthesis of peptides and proteins. The challenging target human thiosulfate:glutathione sulfurtransferase (TSTD1), a 115‐residue protein with only one cysteine at the active site, was synthesized from three segments through a one‐pot C‐to‐N synthetic approach, while its seleno analogue Se‐TSTD1 was synthesized through a one‐pot N‐to‐C synthetic approach.